The house of quality in a minute : a guide to quality function deployment - Madu, Christian N. (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"Quality function deployment (QFD) is an effective tool to help organizations to become more competitive by designing their products and services to satisfy customers' requirements. This book is precise and direct and focuses on the key issues in building the House of Quality otherwise known as Quality Function Deployment (QFD). By reading this book, the manager understands how to solicit customer requirement information, how design requirements are matched to customer requirements, how priorities of customer needs are established, and how activities are benchmarked. Furthermore, this new edition further expands the topic to include process change initiatives on the premise that QFD cannot be achieved if the organization itself is not transformed to achieve customer satisfaction. The manager is guided on how to solve critical problems to achieve customer satisfaction. The book guides the reader to understand how companywide quality activities are related to QFD. This association is often lacking in other presentations that treat QFD as if it is independent of other quality efforts, such as process change initiative. The books will therefore include information on related quality initiatives such as: Identification of customer needs, Benchmarking & re-engineering, Strategic planning, Quality assurance, Stakeholder teams, Concurrent engineering, Cost control & productivity improvement, Six sigma, Process change initiative"--